Bottom‐up and trait‐mediated effects of resource quality on amphibian parasitism. (27th December 2016) - Stephens, Jeffrey P.; Altman, Karie A.; Berven, Keith A.; Tiegs, Scott D.; Raffel, Thomas R.
Abstract: Leaf litter subsidies are important resources for aquatic consumers like tadpoles and snails, causing bottom‐up effects on wetland ecosystems. Recent studies have shown that variation in litter nutritional quality can be as important as litter quantity in driving these bottom‐up effects. Resource subsidies likely also have indirect and trait‐mediated effects on predation and parasitism, but these potential effects remain largely unexplored. We generated predictions for differential effects of litter nutrition and secondary polyphenolic compounds on tadpole ( Lithobates sylvatica ) exposure and susceptibility to Ribeiroia ondatrae, based on ecological stoichiometry and community‐ecology theory. We predicted direct and indirect effects on key traits of the tadpole host (rates of growth, development and survival), the trematode parasite (production of the cercaria infective stages) and the parasite's snail intermediate host (growth and reproduction). To test these predictions, we conducted a large‐scale mesocosm experiment using a natural gradient in the concentrations of nutrients (nitrogen) and toxic secondary compounds (polyphenolics) of nine leaf litter species. To differentiate between effects on exposure vs. susceptibility to infection, we included multiple infection experiments including one with constant per capita exposure. We found that increased litter nitrogen increased tadpole survival, and also increased cercaria production by the snail intermediate hosts, causing opposing effects on tadpole per capita exposure to trematode infection. Increased litter polyphenolics slowed tadpole development, leading to increased infection by increasing both their susceptibility to infection and the length of time they were exposed to parasites. Based on these results, recent shifts in forest composition towards more nitrogen‐poor litter species should decrease trematode infection in tadpoles via density‐ and trait‐mediated effects on the snail intermediate hosts. However, these shifts also involve increased abundance of litter species with high polyphenolic levels, which should increase trematode infection via trait‐mediated effects on tadpoles. Future studies will be needed to determine the relative strength of these opposing effects in natural wetland communities. [Correction added after online publication on 5 January 2017: wording changed to 'which should increase trematode infection via trait‐mediated effects on tadpoles'.] Abstract : This study demonstrates how the theory of ecological stoichiometry can be used to successfully predict the outcomes of complex host–parasite interactions in aquatic ecosystems when the quality of basal resources is known.